2022
DOI: 10.1038/s41598-022-05797-5
|View full text |Cite
|
Sign up to set email alerts
|

m6A-related lncRNAs predict prognosis and indicate immune microenvironment in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a complex hematologic malignancy. Survival rate of AML patients is low. N6-methyladenosine (m6A) and long non-coding RNAs (lncRNAs) play important roles in AML tumorigenesis and progression. However, the relationship between lncRNAs and biological characteristics of AML, as well as how lncRNAs influence the prognosis of AML patients, remain unclear. In this study. In this study, Pearson correlation analysis was used to identify lncRNAs related to m6A regulatory genes, namely m6A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…For example, in hepatocellular carcinoma, tumor typing based on ferroptosis-related lncRNAs (FR-lncRNAs) provided better predictions of prognosis and efficacy of immunotherapy and targeted therapy ( 26 ). In head and neck squamous cell carcinoma (HNSC), the signatures of FR-lncRNAs could also predict patient outcomes ( 27 ), while in acute myeloid leukemia, m 6 A-related lncRNAs could predict the tumor microenvironment (TME) and survival ( 28 ). In addition, lncRNAs also participate in tumor progression by regulating cuprotosis genes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in hepatocellular carcinoma, tumor typing based on ferroptosis-related lncRNAs (FR-lncRNAs) provided better predictions of prognosis and efficacy of immunotherapy and targeted therapy ( 26 ). In head and neck squamous cell carcinoma (HNSC), the signatures of FR-lncRNAs could also predict patient outcomes ( 27 ), while in acute myeloid leukemia, m 6 A-related lncRNAs could predict the tumor microenvironment (TME) and survival ( 28 ). In addition, lncRNAs also participate in tumor progression by regulating cuprotosis genes.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of high-throughput sequencing methods and their widespread use in oncology, disclosing epigenomic irregularities during tumor onset and progression opens the door to the proof of identity of targeted therapies and predictive biomarkers in a range of tumors [ 23 ]. Current attention has been focused on the comprehensive detection of high sequencing results using publicly available databases, which has resulted in several major findings in the diagnosis and therapy of malignancies [ 17 , 24 ]. Conversely, the involvement of m6A regulators in lncRNA deregulation in human cancer is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…FM Zhong et al identified the risk signals related to prognosis of AML patients by using LASSO regression and then constructed a risk model for independent prediction of overall survival in AML patients based on 15 m 6 A-related lncRNAs, including AC025430.1, AFF2-IT1, LINC02593, AC000120.2, AL158163.1, AC048382.1, AL391834, AC008770.3, AL133492.1, AC020916.2 and AJ239328.1. This risk model showed great correlation with clinicopathological factors and immune infiltration levels, which could independently predict AML prognosis, indicating a novel insight in AML treatment [ 182 ].…”
Section: A Modified Lncrnas In Cancersmentioning
confidence: 99%